Autoantibody status in systemic sclerosis patients defines both cancer risk and survival with ANA negativity in cases with concomitant cancer having a worse survival - Watad, Abdulla (Oncoimmunology, 2019)
Background: A higher rate of cancer in systemic sclerosis (SSc) is recognized but the role of SSc-linked autoantibodies status (positive/negative and autoantibody specificities) in the survival of SSc-patients with cancer remains poorly understood. Methods: We utilized the Clalit-Health-Services medical database in a case-control study to evaluate the autoantibody status and specificities of SSc-patients with age- and sex-matched controls with regard to the prevalence of different cancer-subtypes and their impact on mortality. SSc-linked autoantibodies (ANA, anti-centromere, anti-RNP, anti-RNA polymerase III (RNAPIII) and anti-Scl-70) status was assessed in terms of cancer risk and outcome. Results: 2,431 SSc-patients and 12,377 age- and sex-matched controls were included. SSc-patients had a relative risk of cancer of 1.90 (95%CI 1.62-2.24, p < 0.0001) and tended to develop malignancies earlier than controls. RNAPIII and Scl-70 autoantibody were associated with an increased overall cancer risk and after SSc diagnosis risk of cancer, respectively. As expected, SSc-patients with cancer had a risk of death of 2.15 (1.65-2.79) in comparison to SSc-patients without cancer. ANA-positive SSc-patients with cancer had a better prognosis than ANA-negative cases (p = 0.0001). Despite the benefit of ANA-positive status on survival, the anti-Scl-70-positive subgroup with cancer had a significant negative impact on the survival compared to Scl-70-positive cases without cancer, whereas anti-RNAPIII and anti-centromere had no significant impact. Conclusion: ANA positivity is an independent predictor of favorable prognosis in SSc-patients with cancer, possibly suggesting that humoral autoimmunity in SSc with cancer may have some benefit. However, no survival benefit was discernible with the common autoantibodies.